"Under cover of tourism...". Observations and analysis of the Passport Office of the Ministry of Internal Affairs as a complementary policy of religious PRL = "Pod przykryciem turystyki?". Obserwacje i analizy Biura Paszportów Ministerstwa Spraw Wewnętrznych jako elementy uzupełniające politykę wyznaniową PRL - Michalak. Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Design and implementation of tasks PRL religious policy required many specific actions and supporting the work of the Office for Religious Affairs, the security apparatus and specialized agencies of the PZPR. The article discusses the work of the Passport Office of the Ministry of Internal Affairs, as an institution supporting centers of power system operations. Presented source material relates to the observation of behavior West "religious tourists" coming to Polish in the mid-70s of the last century.
Keywords: Passport Office; religious politics; Roman Catholic Church; Lutheran Church; religious minorities; revisionism; Federal Republic of Germany; Biuro Paszportów; polityka wyznaniowa; Kościół Rzymskokatolicki; Kościół Ewangelicko-Augsburski; mniejszości religijne; rewizjonizm; Republika Federalna Niemiec